MSH6 and PMS2 germ-line pathogenic variants implicated in Lynch syndrome are associated with breast cancer. (October 2018) - Roberts, Maegan; Jackson, Sarah; Susswein, Lisa; Zeinomar, Nur; Ma, Xinran; Marshall, Megan; Stettner, Amy; Milewski, Becky; Xu, Zhixiong; Solomon, Benjamin; Terry, Mary Beth; Hruska, Kathleen; et al.
Abstract Purpose An association of Lynch syndrome (LS) with breast cancer has been long suspected; however, there have been insufficient data to address this question for each of the LS genes individually. Methods We conducted a retrospective review of personal and family history in 423 women with pathogenic or likely pathogenic germ-line variants inMLH1 (N = 65), MSH2 (N = 94), MSH6 (N = 140), orPMS2 (N = 124) identified via clinical multigene hereditary cancer testing. Standard incidence ratios (SIRs) of breast cancer were calculated by comparing breast cancer frequencies in our study population with those in the general population (Surveillance, Epidemiology, and End Results 18 data). Results When evaluating by gene, the age-standardized breast cancer risks forMSH6 (SIR = 2.11; 95% confidence interval (CI), 1.56–2.86) andPMS2 (SIR = 2.92; 95% CI, 2.17–3.92) were associated with a statistically significant risk for breast cancer whereas no association was observed forMLH1 (SIR = 0.87; 95% CI, 0.42–1.83) orMSH2 (SIR = 1.22; 95% CI, 0.72–2.06). Conclusion Our data demonstrate that two LS genes, MSH6 andPMS2, are associated with an increased risk for breast cancer and should be considered when ordering genetic testing for individuals who have a personal and/or family history of breast cancer.